Islamic Teaching and Learning Model for Autistic Children in Pesantren Anak Sholeh Baitul Qur’an Ponorogo - Katni, Katni; Sumarni, Sri; Muslim, Aziz (Universitas Muhammadiyah Magelang, 2022)
Autism is a complex developmental disorder that has always been challenging in the education and medicine field. The Islamic teaching and learning model for autistic children requires a special approach. Only a small number of teachers and parents can facilitate autistic children effectively and efficiently. In Indonesia, the number of autistic children is increasing daily, yet there are limited competent teachers and parents to handle them. Meanwhile, the teaching and learning of Islam require educators to select and use multi-approach, multi-media, and multi-methods appropriately to be effective and efficien. This research aimed to examine an experiential-based sociological approach to learning about Islam for Autistic children at Pesantren Anak Sholeh Baitul Qur’an Ponorogo, Indonesia, using a qualitative method. A purposive sampling technique was used to select subjects, specifically teachers and children. The data was collected using interviews, observation, and documentation.‎ The results showed that the experience-based habitus sociology approach effectively teaches autistic children in three cognitive, affective, and psychomotor aspects. Monitoring and intensive evaluation to assess the activities at home and school requires the cooperation of parents and teachers and follow-up efforts to enhance learning.